(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
The article explores the experience of the United Kingdom, Germany, Turkey, China, Ukraine, Kazakhstan, Russia, Kyrgyzstan, Tajikistan, Belarus in preventing and exposing the crime of theft from housing, and develops substantiated proposals and recommendations.